Canonical Correlations on Positive and Negative Attitudes of Computer-Based Statistics among Business Students - Tri Effiyanti; Gaffar Hafiz Sagala; Sukirno; Heri Retnawati (Economics Education Department Universitas Negeri Semarang, 2024)
This study aims to investigate the canonical relationship between positive and negative attitudes of economics and business students when using computer-based analytical tools. The subjects of this study were students of the Faculty of Economics and Business in Medan. Samples were taken from two universities, including state universities and private universities. Using a random sampling technique, this study collected 247 responses, consisting of 47 male and 200 female respondents. The data in this study were collected using a questionnaire with a 5-Likert scale and analyzed by canonical correlation. The results of the canonical correlation analysis in this study revealed that Perceived Usefulness (PU) and Perceive Enjoyment (PE) were critical predictors of the construct set of positive attitudes. At the same time, Strain (ST) and Negative Affectivity (NA) were essential predictors of the formation of negative attitudes among users when using computer-based statistical tools. This study produces a new insight related to attitude toward Information Technology (IT) in a specific task, namely statistical analysis. This study also has practical recommendations for universities and lecturers to invest in and use statistical software that is easy and convenient for teaching statistics.